Solubilization profiles of metal ions from bioleaching of sewage sludge as a function of pH - Villar, L. D.; Garcia, O. (Kluwer Academic Publ, 2002)
Two patterns of solubilization of metal ions resulting from bioleaching of sewage sludge by sulphur-oxidizing Thiobacillus spp. were established as a function of pH. Chromium and copper ions required a pH of 2-3 to initiate their solubilization, whereas nickel and zinc ions had their solubilization initiated at pH 6-6.5. The patterns obtained were independent of the sludge solids concentrations investigated (10, 17, 25, 32.5 and 40 g l(-1)).
Keywords: bioleaching; heavy metals; sewage sludge; solubilization profile; sulphur-oxidizing bacteria